2016
DOI: 10.1093/ndt/gfw078
|View full text |Cite
|
Sign up to set email alerts
|

Systemic complement activation and complement gene analysis in enterohaemorrhagicEscherichia coli-associated paediatric haemolytic uraemic syndrome

Abstract: Complement activation at the acute phase of EHEC-HUS, indicated by increased levels of sC5b-9, predicts a poor outcome. Complement alterations appear to be more frequent in patients with EHEC-HUS than previously thought and are suspected to have a role in the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…This complement activation normalized to control levels in remission, except for C3bBbP in STEC-HUS patients. Our results corroborate previous reports of complement activation in children with STEC-HUS [19–23]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This complement activation normalized to control levels in remission, except for C3bBbP in STEC-HUS patients. Our results corroborate previous reports of complement activation in children with STEC-HUS [19–23]. …”
Section: Discussionsupporting
confidence: 93%
“…We were surprised to see that in almost 30 % of STEC-HUS patients, a genetic complement aberration could be identified. Several case reports of STEC-HUS patients with complement mutations have been published [35, 3942], but so far, only one larger cohort was investigated; in 3/25 (12.0 %) STEC-HUS patients, a mutation was identified [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty years later, the demonstration that atypical hemolytic uremic syndrome (aHUS) was a disease of complement alternative pathway dysregulation (4), and that complement blockade therapy improved aHUS prognosis (5), gave a new impetus to the question of a role of complement activation in Shiga toxin-associated HUS. Indeed, elevated plasma levels of complement activation biomarkers were documented at the acute phase of post diarrheal/typical/Shiga toxin HUS (6)(7)(8)(9)(10)(11). In vitro studies and animal models experiments demonstrated that Shiga toxin generates a cascade of endothelial/podocyte injury, complement activation, expression of chemokines and adhesion molecules, neutrophil activation, and thrombus formation (7,(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In nine of them, genetic screening was motivated by an unusually severe outcome, relapses, or post-transplant recurrence, suggesting that STEC infection triggers aHUS onset and/or preexisting complement variants amplify Shiga toxin-induced complement activation and endothelial/podocyte damage, and worsen disease severity (20)(21)(22)(23)(24)(25)(26)(27). However, seven reported patients who had complement variants had a favorable outcome (9,10,28), leaving the issue of the role of genetics in Shiga toxinassociated HUS unclear.…”
Section: Introductionmentioning
confidence: 99%